2021
DOI: 10.1177/1055665621998394
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin B12 Status and Risk of Cleft Lip and Cleft Palate Birth Defects in Tamil Nadu State, India

Abstract: Background and Objective: The causal role of maternal nutrition in orofacial clefts is uncertain. We tested hypotheses that low maternal vitamin B12 and low folate status are each associated with an increased risk of isolated cleft lip with or without cleft palate (CL±P) in a case–control study in Tamil Nadu state, India. Methods: Case-mothers of CL±P children (n = 47) and control-mothers of unaffected children (n = 50) were recruited an average of 1.4 years after birth of the index child and plasma vitamin B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
(112 reference statements)
0
7
0
1
Order By: Relevance
“…with the incidence of CL and or CLP (12). The study stated that a person deficient in vitamin B12 had a 6.…”
Section: Icmedhmentioning
confidence: 99%
See 1 more Smart Citation
“…with the incidence of CL and or CLP (12). The study stated that a person deficient in vitamin B12 had a 6.…”
Section: Icmedhmentioning
confidence: 99%
“…Elevated homocysteine is a strong risk factor for embryonic toxicity and the development of congenital defects, especially in the form of CL and/or CLP (11). A research conducted by Munger (2021) stated that there was a close difference between deficiency or low levels of vitamin B12…”
Section: Icmedhmentioning
confidence: 99%
“…Tana et al reported that compared with the control group, exercise reduced the prevalence of the DDs in the offspring of GBD mice by 34.5% [80] . Addition to exercise, intaking trace elements is also one of the available approaches to prevent DDs [81][82][83] . This is owing to the pivotal role of trace elements in retaining redox homeostasis and regulating signal transduction pathways and immune function in healthy growth and development of body [84] .…”
Section: Diet Exercisementioning
confidence: 99%
“…It is generally known that folate deficiency results in pregnancy-related complications and abnormal embryonic development with congenital defects, like neural tube defects (NTDs). However, low vitamin B 12 status was also found to be associated with the risk of NTDs (Molloy et al, 2009), cleft lip/palate (Munger et al, 2021), early recurrent abortion (Reznikoff-Etiévant et al, 2002), preterm birth and low birth weight (Rogne et al, 2017). For review of vitamin B 12 deficiency in pregnancy, see Van Sande et al (2013).…”
Section: Biochemical Basis Of the Reproductive Risks Of N2omentioning
confidence: 99%